Editorial: Metabolomics in Infectious Diseases - Mahbuba Rahman (198499) (2022)
Metabolomics is an important emerging field of omics technology. While the metabolic pathways in prokaryotic or disease-causing agents are relatively simple compared to those of mammalian hosts, metabolite pools reflect the instant (snapshot) status of cells under healthy or diseased conditions or when infecting the host (Tan et al., 2007) (Lee et al., 2015). In humans, immune cells play a major role in the defense against microbial infection. The metabolic pathways of immune cells are under the stringent control of metabolites and small molecules under a quiescent or active state. Any subtle change in the gene expression during the diseased condition can affect the downstream pathways that consist of proteins and metabolites. Metabolites belong to different chemical groups such as amino acids, organic acid, lipids, or amines. Due to their close association with the cellular system, the detection of metabolites can provide the accurate status of the cell and can also be used as biomarkers of disease or drug targets (Rahman and Hasan 2014). Considering the importance of the field of metabolomics, the current research topic aimed to collect articles where metabolites and metabolite detection tools are used for different purposes in infectious disease. Articles published in this issue show how metabolomics can be used as biomarkers of disease during pandemics, use of metabolomics in clinical management of infectious disease, during metabolomics co-infection of virus and bacteria, metabolites associated with inflammatory disease, and specific proteins associated with transport molecules during communicable and non-communicable disease. Other Information Published in: Frontiers in Genetics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fgene.2022.875835